(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes innovative methods of teaching foreign languages and pedagogy in the modern education system. The article examines the impact of interactive learning technologies, gamification, artificial intelligence-based learning platforms and multimedia tools on the learning process. In addition, modern pedagogical approaches and their effectiveness are analyzed.